EKSISTENSI UU NO. 20 TAHUN 2003 TENTANG SISTEM PENDIDIKAN NASIONAL DALAM MENYELESAIKAN KASUS KEKERASAN TERHADAP SISWA YANG DILAKUKAN OLEH OKNUM KEPALA SEKOLAH - Anggadia Permata Wardana, Ni Putu; Purwanti, Putu (Kertha Wicara : Journal Ilmu Hukum; Vol. 03, No. 03, Juli 2014)
This paper, titled "The Existence of the Act No. 20 Year 2003 on National Education System with regard to Resolving Cases of Violence against Students Done by Unscrupulous Headmaster ". This paper uses the method of normative research. The paper discusses the setting and completion of criminal cases committed by unscrupulous school principals. The conclusion that could be drawn from this paper is that the Headmaster has violated the National Education System Rules and has been deactivated from duties and could be penalized of criminal sanctions in the form of imprisonment of 5 years and a fine of two hundred million.
Keywords: Education System, Violence, The Existence